SPATIAL VARIATIONS OF SEISMIC WAVE ATTENUATION IN THE SOUTH BAIKAL BASIN AND ADJACENT AREAS (BAIKAL RIFT) - A. A. Dobrynina; P. A. Predein; V. A. Sankov; Ts. A. Tubanov; D. P.-D. Sanzhieva; E. A. Gorbunova (Геодинамика и тектонофизика)
Our detailed study of the crust and upper mantle of the South Baikal basin focused on seismic coda and seismic S-waves attenuation and estimated seismic quality factor (QS and QC), frequency parameter (n), attenuation coefficient (δ), total attenuation (QT), and the ratio of two components the total attenuation: intrinsic attenuation (Qi), and attenuation due to scattering caused by the inhomogeneities of the medium (QSC). We calculated the sizes of inhomogeneities revealed in the block medium, which put their effect on the attenuation of seismic waves in different frequency ranges. The seismic wave attenuation field was analyzed in comparison with the geological and geophysical characteristics of the medium, and a direct relationship was established between attenuation, composition and active processes in the crust and upper mantle of the studied area. According to the estimated intrinsic attenuation (Qi) and scattering attenuation (QSC) contributions into the total attenuation, intrinsic attenuation is generally dominant in the studied area, while the QSC component increases in the areas of large active faults.